Overexpression of PSY1 increases fruit skin and flesh carotenoid content and reveals associated transcription factors in apple (Malus × domestica) - Ampomah-Dwamena, Charles; Tomes, Sumathi; Thrimawithana, Amali H.; Elborough, Caitlin; Bhargava, Nitisha; Rebstock, Ria; Sutherland, Paul; Ireland, Hilary; Allan, Andrew C.; Espley, Richard V. (Frontiers in Plant Science, 2022)
The plant carotenoid biosynthetic pathway is well characterised, but knowledge of its transcriptional regulation is still emerging. We overexpressed phytoene synthase (PSY1), which controls the key rate-limiting biosynthetic step, in apple and analysed its effects in transgenic fruit using two approaches. Firstly, the effects of PSY overexpression on carotenoid accumulation and gene expression was assessed in fruit at different development stages. Secondly, the effect of light exclusion on PSY-induced fruit carotenoid accumulation was examined. PSY overexpression increased carotenoid content in transgenic fruit skin and flesh, with beta-carotene being the most prevalent carotenoid compound. Light exclusion by fruit bagging reduced carotenoid content overall, but carotenoid content was still higher in bagged PSY fruit than in bagged controls. In tissues overexpressing PSY, plastids showed accelerated chloroplast to chromoplast transition as well as high fluorescence intensity, consistent with increased number of chromoplasts and carotenoid accumulation. Surprisingly, the expression of other carotenoid pathway genes was elevated in PSY fruit, suggesting a feed-forward regulation of carotenogenesis when this enzyme step is mis-expressed. Transcriptome profiling of fruit flesh identified differentially expressed transcription factors (TFs) that also were co-expressed with carotenoid pathway genes. A comparison of differentially expressed genes from both the developmental series and light exclusion treatment revealed six candidate TFs exhibiting strong correlation with carotenoid accumulation. This combination of physiological, transcriptomic and metabolite data sheds new light on plant carotenogenesis and TFs that may play a role in regulating apple carotenoid biosynthesis.